2021
DOI: 10.1111/soru.12330
|View full text |Cite
|
Sign up to set email alerts
|

Origin food schemes and the paradox of reducing diversity to defend it

Abstract: Origin food schemes (OFS) aim to protect and promote a unique product resulting from a specific place and know-how whose qualities are objectified in the product specifications. This paper explores the standardisation effects of OFS on the diversity of local practices and knowledge by analysing the emergence of the specifications of four origin cheeses recognised as Geographical Indications and Slow Food Presidia (Chefchaouen goat cheese in Morocco, Piacentinu Ennese in Italy, and Béarn mountain cheese and Oss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Furthermore, OFS promote direct relationships between producers and consumers, and, by doing so, foster exchanges and creation of knowledge between them [65]. Our findings showed that GIs and Presidia can be considered 'communities of practice' which include consumers, and are strengthened by practical experiences, with different casedependent results [53]. Although sharing knowledge within a renewed network of personal and practical relationships is a main feature of both studied OFS, our results show that Slow Food surpasses the GI model in this respect for two reasons.…”
Section: Food Culture: Gap Between Production and Consumption Knowledgementioning
confidence: 73%
See 3 more Smart Citations
“…Furthermore, OFS promote direct relationships between producers and consumers, and, by doing so, foster exchanges and creation of knowledge between them [65]. Our findings showed that GIs and Presidia can be considered 'communities of practice' which include consumers, and are strengthened by practical experiences, with different casedependent results [53]. Although sharing knowledge within a renewed network of personal and practical relationships is a main feature of both studied OFS, our results show that Slow Food surpasses the GI model in this respect for two reasons.…”
Section: Food Culture: Gap Between Production and Consumption Knowledgementioning
confidence: 73%
“…(i) Participant observation in the production and market of origin cheese, including on-farm cheesemaking with selected producers, farmers markets and Slow Food events, to unfold the practical experience of different communities and the actor's point of view; (ii) Semi-structured interviews with producers, technicians, trainers and public administrators to determine the governance ideal type of both Presidia and GIs (motivation associated to launch of the initiative, actors' involvement and management system), and the most relevant challenges they are facing (estimated results and pitfalls); (iii) Informal interviews with producers, consumers and cooks designed along 3 axes: background (context, motivation associated to the initiative, estimated results), discourses on CB (understanding and value), practices of CB (learning experiences, production practices, changes); (iv) Written sources that helped to design and develop the field analysis and the following data analysis. These mainly ethnographic data are extensively presented and discussed in previous works [53,54]. The present paper results from the cross-comparison of such multi-site information to reflect on each case study from a broader perspective and to allow for the development of an explanatory model.…”
Section: Data Collection: An Ethnographic Enquirymentioning
confidence: 99%
See 2 more Smart Citations
“…The entry of the products into new social and economic networks requires adaptations to consumer tastes and regulations posed by the institutional actors therein [103].…”
Section: Eroding Traditional Values and Relationshipsmentioning
confidence: 99%